The Evolution of Horror in the Twenty-First Century - Bacon, Simon (Lexington Books, 2023)
The Evolution of Horror in the Twenty-First Century examines the intimate connections between the horror genre and its audience’s experience of being in the world at a particular historical and cultural moment. This book not only provides frameworks with which to understand contemporary horror, but it also speaks to the changes wrought by technological development in creation, production, and distribution, as well as the ways in which those who are traditionally underrepresented positively within the genre- women, LGBTQ+, indigenous, and BAME communities - are finally being seen and finding space to speak.